2016
DOI: 10.1016/j.jcin.2016.08.041
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lesion Location on the Diagnostic Accuracy of Adenosine-Free Coronary Pressure Wire Measurements

Abstract: The cFFR, iFR, and Pd/Pa are less accurate in LM/pLAD compared with other lesion locations, likely related to the larger amount of myocardium supplied by LM/pLAD. Nevertheless, cFFR provides the best diagnostic accuracy among the adenosine-free indices, regardless of lesion location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…Finally, Kobayashi et al have already reported on the relationship between left main and proximal LAD stenoses and greater discordance between iFR and FFR; in this setting, the larger myocardial mass subtended by these vessels may result in greater coronary flow variation between resting and hyperemic conditions compared with vessels subtending smaller amounts of myocardium and therefore a greater chance for discordance (FFR+/iFR‐). On the other hand, in older patients, FFR across a similar angiographic stenosis is higher than in younger patients, perhaps due to a greater degree of microvascular dysfunction in older patients .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Kobayashi et al have already reported on the relationship between left main and proximal LAD stenoses and greater discordance between iFR and FFR; in this setting, the larger myocardial mass subtended by these vessels may result in greater coronary flow variation between resting and hyperemic conditions compared with vessels subtending smaller amounts of myocardium and therefore a greater chance for discordance (FFR+/iFR‐). On the other hand, in older patients, FFR across a similar angiographic stenosis is higher than in younger patients, perhaps due to a greater degree of microvascular dysfunction in older patients .…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the large amount of myocardium supplied by LAD and emphasizes the need for physiological assessment to identify LAD lesions that may benefit from revascularization. Kobayashi et al documented that all alternative pressure indices (contrastFFR, iFR, and resting Pd/Pa) showed impaired accuracy for combined left main coronary artery/proximal LAD disease with FFR as Reference . Hence, there may be a theoretical concern that nonhyperemic flow‐based and angiography‐derived assessment underestimates the severity of proximal LAD lesions by not appreciating the potential large increase in flow during hyperemia where a high peak flow leads to a large pressure gradient and thus a low FFR .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the greatest increments in transstenotic flow occur in vessel locations with the largest amounts of downstream myocardium, these situations occur most frequently in proximal left anterior descending artery or left main stem stenoses. 10,11 Such positive FFR values are similar to a young patient with mild aortic stenosis on echocardiographic assessment developing severe aortic stenosis in the same setting with increased flow during exercise. We do not perform aortic valve replacement in such circumstances because we know this measurement is an anomaly caused by a huge increase in flow.…”
Section: Ffr: a Surrogate Measure Of Coronary Flowmentioning
confidence: 63%
“…With FFR, the paradox exists in which patients with the mildest stenoses, the healthiest microcirculations, and the greatest increments in coronary flow can still generate low FFR values. Furthermore, because the greatest increments in transstenotic flow occur in vessel locations with the largest amounts of downstream myocardium, these situations occur most frequently in proximal left anterior descending artery or left main stem stenoses . Such positive FFR values are similar to a young patient with mild aortic stenosis on echocardiographic assessment developing severe aortic stenosis in the same setting with increased flow during exercise.…”
Section: Ffr: a Surrogate Measure Of Coronary Flowmentioning
confidence: 94%